MiR‐872‐5p/FOXO3a/Wnt signaling feed‐forward loop promotes proliferation of endogenous neural stem cells after spinal cord ischemia–reperfusion injury in rats. Issue 2 (6th January 2023) - Li, Yuanyuan; Zhang, Shaoqiong; Cui, Kaile; Cao, Linyan; Fan, Yiting; Fang, Bo
Abstract: The activation of endogenous neural stem cells (NSCs) is considered an important mechanism of neural repair after mechanical spinal cord injury; however, whether endogenous NSC proliferation can also occur after spinal cord ischemia–reperfusion injury (SCIRI) remains unclear. In this study, we aimed to verify the existence of endogenous NSC proliferation after SCIRI and explore the underlying molecular mechanism. NSC proliferation was observed after SCIRI in vivo and oxygen–glucose deprivation and reperfusion (OGD/R) in vitro, accompanied by a decrease in forkhead box protein O 3a (FOXO3a) expression. This downward trend was regulated by the increased expression of microRNA‐872‐5p (miR‐872‐5p). miR‐872‐5p affected NSC proliferation by targeting FOXO3a to increase the expression of β‐catenin and T‐cell factor 4 (TCF4). In addition, TCF4 in turn acted as a transcription factor to increase the expression level of miR‐872‐5p, and knockdown of FOXO3a enhanced the binding of TCF4 to the miR‐872‐5p promoter. In conclusion, SCIRI in vivo and OGD/R in vitro stimulated the miR‐872‐5p/FOXO3a/β‐catenin‐TCF4 pathway, thereby promoting NSC proliferation. At the same time, FOXO3a affected TCF4 transcription factor activity and miR‐872‐5p expression, forming a positive feedback loop that promotes NSC proliferation.